2016
DOI: 10.1007/s00415-016-8074-7
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam and thiopental for the treatment of refractory status epilepticus: a retrospective comparison of efficacy and safety

Abstract: Current management guidelines for refractory status epilepticus (RSE) recommend the use of intravenous continuous anesthetic therapy, but there is little evidence to guide the selection of the most efficacious and safest drug. We conducted a retrospective study to evaluate the efficacy and safety of midazolam versus thiopental for treatment of RSE. Retrospective case-control series of prospectively identified patients treated with midazolam or thiopental for RSE between January 2007 and December 2014. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 41 publications
3
48
0
2
Order By: Relevance
“…Especially pentobarbital has been linked to the development of hypotension requiring prolonged duration of mechanical ventilation and vasopressor therapies,76 which have in turn been associated with poor long‐term outcome 54. Continuous infusion of thiopental was also associated with more frequent adverse events and worse outcome at 6 months compared to continuous infusions of midazolam 77. However, it is discussed whether the association with negative outcomes is effectively due to the use of IVADs, or due to confounding by indication, as patients who require continuous infusions are probably more critically ill 78.…”
Section: Factors Affecting Outcomementioning
confidence: 99%
“…Especially pentobarbital has been linked to the development of hypotension requiring prolonged duration of mechanical ventilation and vasopressor therapies,76 which have in turn been associated with poor long‐term outcome 54. Continuous infusion of thiopental was also associated with more frequent adverse events and worse outcome at 6 months compared to continuous infusions of midazolam 77. However, it is discussed whether the association with negative outcomes is effectively due to the use of IVADs, or due to confounding by indication, as patients who require continuous infusions are probably more critically ill 78.…”
Section: Factors Affecting Outcomementioning
confidence: 99%
“…Although the STESS model requires seizure type and EEG information in case of nonconvulsive SE and EMSE model is more complicated, requires relatively more time and always needs advanced imaging/EEG to fulfill the model, our mode is less time-consuming to use. 20 These findings indicate that anemia may be a predictor of refractory SE. The independent comorbidities were heart disease, central nervous system (CNS) infection, cancer, chronic renal failure, and anemia, whereas the significant SE complications were shock, acute renal failure, septicemia, pneumonia, and respiratory failure.…”
Section: Discussionmentioning
confidence: 90%
“…Without EEG, there were 3 mainly clinical factors for SE mortality including advanced age, comorbidities, and the presence of SE complications. 20 Neither the STESS model nor the EMSE model includes complications of SE. Advanced age has been reported to be the predictor for SE mortality in several studies including both those that use STESS and those that use EMSE predictive models.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our cohort, the duration of TC in all these studies had a relatively wide range of treatment duration anywhere from 24 to 96 hours. The rate of seizure recurrence following treatment with TC was found to be between 10% and 20%, but none of these studies looked at seizure recurrence in association with duration of TC . Only one study analyzed the association between duration of TC and various clinical outcomes, and found that treatment duration for greater than 20 hours was associated with poor functional outcome and death .…”
Section: Discussionmentioning
confidence: 99%
“…T 2 is the second time point at which the dose of anesthetic started to develop a significant downward trend, defined by a drop of at least 20% of the hourly infusion rate in three subsequent hours and an ultimate endpoint of 0 (Figure ). Similar to prior studies comparing the efficacy and safety of different anesthetics, the maximum steady dose of anesthetic was converted to a time‐ and weight‐based unit (µg/kg/min) across all anesthetic agents utilized in the first trial of TC …”
Section: Methodsmentioning
confidence: 99%